2009
DOI: 10.1248/bpb.32.993
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of A-769662, a Novel Activator of AMP-Activated Protein Kinase, on 3T3-L1 Adipogenesis

Abstract: Obesity is a chronic metabolic disorder caused by an imbalance between energy intake and expenditure. It is a major known risk factor for many chronic diseases such as type 2 diabetes, hypertension and atherosclerosis.1) Therefore, it has become a major obstacle of improving human health and life quality. Obesity is characterized by a pathologic growth of adipose tissues, which is intrinsically a consequence of adipocyte hypertrophy and differentiation. 2)Studies on several established immortal preadipocyte ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…[15][16][17] In a previous report, we observed that CAPE treatment dose-dependently suppressed oil droplet accumulation, reduced the size of droplets and could significantly inhibit triglyceride deposition in 3T3-L1 cells. These results indicate that CAPE administration may be effective for adipocytes differentiation.…”
Section: Discussionmentioning
confidence: 79%
“…[15][16][17] In a previous report, we observed that CAPE treatment dose-dependently suppressed oil droplet accumulation, reduced the size of droplets and could significantly inhibit triglyceride deposition in 3T3-L1 cells. These results indicate that CAPE administration may be effective for adipocytes differentiation.…”
Section: Discussionmentioning
confidence: 79%
“…These effects were characterized by increased mitochondrial density and by the presence of mitochondria with more defi ned cristae in the WAT of AICAR-treated animals. This was also accompanied by time-dependent upregulation of FA oxidation in ING and RP but not in EPI been demonstrated in 3T3-L1 adipocytes that the content and/or activity of ACC are decreased in cells treated with various AMPK agonists, along with other adipogenic markers required for differentiation of preadipocytes into mature fat cells ( 4,5 ). In our study, animals begin AICAR treatment at ā€«Łā€¬ 6 to 7 weeks in age, which may have affected adipogenesis in preadipocytes present in the WAT.…”
Section: Discussionmentioning
confidence: 87%
“…AMPK has also been shown to block adipocyte differentiation in the early stages by inhibiting clonal expansion, which is a critical step for adipogenesis to occur ( 4,5 ). Additionally, treatment of preadipocytes with pharmacological agents to activate AMPK prevents the expression of late adipogenic markers, fatty acid synthase, acetyl-CoA carboxylase (ACC), and transcription factors peroxisome proliferator-activated receptor (PPAR) ā„ 1/2 and CCAAT-enhancer-binding protein (C/EBP) ā£ which are required for the synthesis and storage of lipids in mature adipocytes ( 4,5 ). AMPK also phosphorylates and activates PPAR-ā„ coactivator-1 ā£ (PGC-1 ā£ ) and promotes mitochondrial biogenesis in skeletal muscle ( 6 ).…”
Section: Assessment Of the Anorectic Response To Leptinmentioning
confidence: 99%
“…In this way, AMPK functions as an energy sensor, restoring energy levels by phosphorylating a wide array of substrates (Carling 2004, Carling et al 2008. Several reports have demonstrated that some activators of AMPK, including AICAR and A-769662, inhibit adipogenesis (Giri et al 2006, Zhou et al 2009, Lee et al 2011. Both PKA and PKB, which are activated during the differentiation of adipocytes, have been suggested to inhibit the activity of AMPK by phosphorylating S485 on the catalytic subunit (Hurley et al 2006).…”
mentioning
confidence: 99%